Overexpression of p16INK4a Serves as Prognostic Marker in Squamous Cell Vulvar Cancer Patients Treated With Radiotherapy Irrespective of HPV-Status - Arians, Nathalie; Prigge, Elena-Sophie; Nachtigall, Tereza; Reuschenbach, Miriam; Koerber, Stefan Alexander; Debus, Juergen; von Knebel Doeberitz, Magnus; Lindel, Katja (Frontiers in Oncology, 2019)
Purpose: We aimed to evaluate the impact of HPV-driven carcinogenesis on outcome in vulvar squamous cell carcinoma patients (VSCC) treated with radiotherapy. Methods and Materials: Analysis of clinical, pathological and treatment data, HPV DNA-detection and -genotyping as well as p16INK4a immunohistochemistry were performed in 75 VSCC patients. Kaplan–Meier-method was used to estimate locoregional control (LC), Progression-free survival (PFS) and Overall Survival (OS). Univariate survival time comparisons were performed using the log-rank-test. Chi-square/Fisher exact test was used to assess correlations between HPV DNA and p16INK4a data, pathological, clinical and treatment characteristics. Results: 23/75 (30.67%) of all women had locoregional relapse, 7/75 (9.3%) systemic recurrence and 35/75 (46.67%) died after a median follow-up of 26.4 months. 21.3% of the tumors were HPV DNA-positive, mostly (93.75%) for the high-risk (HR) HPV type 16. 25.3% showed p16INK4a-overexpression. 17.3% showed concomitant HPV DNA- and p16INK4a-positivity (cHPPVC). Patients with p16INK4a-overexpression, irrespective of the HPV DNA status, showed significantly better PFS (5-year-PFS 69.3% vs 39.2%, p=0.045), LC (5-year-LC 86.7% vs 56.7%, p=0.033) and a strong trend for better OS (5-year-OS 75.6% vs 43.9%, p=0.077). Patients with cHPPVC showed a trend for better PFS (5-year-PFS 72.7% vs 41.3%, p=0.082) and OS (5-year-OS 81.1% vs 45.7% , p=0.084) but no significant benefit for LC. Conclusions: Patients with cHPPVC, indicating an etiological relevance of HPV in the respective tumors, showed a better, albeit not significant, prognosis. The sole detection of p16INK4a-overexpression is a prognostic factor for survival in vulvar cancer and indicates better prognosis after radiotherapy, independent of detection of HPV DNA. p16INK4a should be used as surrogate marker for HPV-driven carcinogenesis in vulvar cancer with caution.